(untitled) (Research, Society and Development, 2022)
Primary Study Objective: the aim of this review was to filter current research written in English from 2010 to 2020 to elucidate the following question: what are the psychological and neurophysiological effects of inhaled aromatherapy on human health? Papers were selected based on PRISMA recommendations from Pubmed, Science Direct and Virtual Health Library databases. PICO technique and PROSPERO registration were also considered during the elaboration of this Systematic Review. Setting: schools, hospitals, clinics and dental offices. Participants: children, adults and elderly. Intervention: Essential oil inhalation. Primary Outcome Measures: Psychological approaches (eg. psychometric scales and cognitive tasks) and neurophysiological approaches (eg. heart rate variability/HRV and salivary cortisol). Results: From 1.458 papers, 14 were selected for final analysis and displayed in a table containing the following information: Score based on credibility criteria, authors, country, group, sex, age, objective, procedure and outcome. Conclusion: Aromatherapy mainly modulates the autonomic nervous system, with a predominance of parasympathetic activation and contributes to reduce cortisol and to increase melatonin levels. In addition, it can alleviate anxiety, depression and insomnia.